Diversification of Agriculture through Clonal Eucalyptus - Sapra, R. K. (Indian Forester, 2008)
A silent revolution has taken place in productivity and profitability of plantations through clonal Eucalyptus, with productivity more than double compared to seed-route plantations. The clonal plantations under rain-fed conditions are safer investment, while the irrigated clonal plantations under agro-forestry models are more profitable as compared to agricultural crops. The risks and direct labour associated with agricultural crops are greater as compared to clonal plantations. The water requirement of Eucalyptus plantations is lesser as compared to many agricultural crops like paddy. The clonal Eucalyptus plantations can be popularized through planting of genetically improved clonal plants on degraded forest lands, establishing clonal demonstration plots, and training forest officials in extension activities. The clonal plantations will certainly help in conserving water resources, diversifying agriculture in Indo-Gangetic plains, generating large volumes of superior timber and employment opportunities through agro-forestry plantations and promoting wood-based industries.